2008
DOI: 10.1364/oe.16.015228
|View full text |Cite
|
Sign up to set email alerts
|

High performance EUV multilayer structures insensitive to capping layer optical parameters

Abstract: We have designed and tested a-periodic multilayer structures containing protective capping layers in order to obtain improved stability with respect to any possible changes of the capping layer optical properties (due to oxidation and contamination, for example)-while simultaneously maximizing the EUV reflection efficiency for specific applications, and in particular for EUV lithography. Such coatings may be particularly useful in EUV lithographic apparatus, because they provide both high integrated photon flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…A large amount of work has been done on multilayers for mask illumination and replication [1,59] in extreme ultraviolet lithography (EUVL), but so less thought has been given to inspection of the masks and produced components. Defects in EUVL masks can occur in both the absorber patterns and the multilayer-coated mask blanks, and inspection is essential as the number of defects has to be minimized.…”
Section: Euv Intensity Beam Splittermentioning
confidence: 99%
See 2 more Smart Citations
“…A large amount of work has been done on multilayers for mask illumination and replication [1,59] in extreme ultraviolet lithography (EUVL), but so less thought has been given to inspection of the masks and produced components. Defects in EUVL masks can occur in both the absorber patterns and the multilayer-coated mask blanks, and inspection is essential as the number of defects has to be minimized.…”
Section: Euv Intensity Beam Splittermentioning
confidence: 99%
“…Multilayers, consisting of periodic/aperiodic nanometer-scale stacks of two or more alternating materials deposited on a substructure, fill the gap between mirror and crystal by realizing high near-normal incidence reflectivity in EUV [1,2] and soft X-ray [3,4] regimes, and also challenge diffraction-limited focusing in hard X-ray regime by multilayer Kirkpatrick-Baez [5] or multilayer Laue lens [6] systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Capped Mo/Si multilayers, that can reach up to 26% reflectance at 30.4 nm [7,8] -Ir/Si multilayer, that can achieve up to 24% peak reflectance [9] -SiC/Mg multilayer, that has a peak reflectance of 40% [10]. SiC/Mg multilayers have been demonstrated to be unstable over time [11], therefore their applicability to a long term mission seems not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…40 Apart from EUV reflectance simulations, there are several reported studies where the EUV reflectance is experimentally measured, before and after EUV exposure, (or similar ebeam exposure) in a water vapor environment from Si-terminated Mo/Si MLMs, capped with different protective layers (with or without diffusion barriers) such as Ru, 128 Ru/Mo, 128,129 130 Most of these studies not only measure the EUV reflectance upon exposure, but also investigate the EUV-induced oxidation resistance of the protective material (and/or underlying multilayer). 41,49,128,131 In this line, there are other studies reported that test different protective materials against oxidation on a multilayer (or a single Mo or Si layer, mimicking the last layer of the multilayer), not only by EUV (or e-beam) exposure in presence of water, 132 but also by atomic oxygen, 133 by oxygen plasma, 134 or by ambient air.…”
Section: Euvl Opticsmentioning
confidence: 99%